2004
DOI: 10.1073/pnas.0402981101
|View full text |Cite
|
Sign up to set email alerts
|

A rare genotype of Cryptococcus gattii caused the cryptococcosis outbreak on Vancouver Island (British Columbia, Canada)

Abstract: Cryptococcus gattii causes life-threatening infection of the pulmonary and central nervous systems in hosts with normal immunity and traditionally has been considered to be restricted geographically to tropical and subtropical climates. The recent outbreak of C. gattii in the temperate climate of Vancouver Island, BC, Canada, led to a collaborative investigation. The objectives of the current study were to ascertain the environmental source of the outbreak infections, survey the molecular types of the outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
733
4
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(780 citation statements)
references
References 24 publications
27
733
4
16
Order By: Relevance
“…For example, Cryptococcus gatti was traditionally considered to be restricted to tropical and subtropical climates; however, there is increasing evidence that it can be dispersed via the atmosphere even to colder areas such as the Northwest USA (Kidd et al 2004; Byrnes et al 2010). Other investigations into the ecological niches of these opportunistic pathogens have revealed a global distribution (Chen et al 2014) often associated with reservoirs such as guano (Nielsen et al 2007), Eucalyptus trees (Ellis and Pfeiffer 1990a), and Cassia trees (Lazera et al 2000; Granados and Castañeda 2005).…”
Section: Global Aerial Dispersal Of Naganishia Speciesmentioning
confidence: 99%
“…For example, Cryptococcus gatti was traditionally considered to be restricted to tropical and subtropical climates; however, there is increasing evidence that it can be dispersed via the atmosphere even to colder areas such as the Northwest USA (Kidd et al 2004; Byrnes et al 2010). Other investigations into the ecological niches of these opportunistic pathogens have revealed a global distribution (Chen et al 2014) often associated with reservoirs such as guano (Nielsen et al 2007), Eucalyptus trees (Ellis and Pfeiffer 1990a), and Cassia trees (Lazera et al 2000; Granados and Castañeda 2005).…”
Section: Global Aerial Dispersal Of Naganishia Speciesmentioning
confidence: 99%
“…grubii, however, have not been documented. C. gattii (serotypes B and C) was originally predominantly found in subtropical regions but a newly recombined serotype B clone has emerged over the past 10 years as a cause of cryptococcal infections in animals and otherwise healthy humans on Vancouver Island [17]. More recently, this epidemic is spreading to the Pacific Northwest of the United States [18,19].…”
Section: Classification Of Cryptococcus Neoformans and C Gattiimentioning
confidence: 99%
“…It is interesting to observe that the mating process occurred in isolates of both mating types in a similar ratio, 9:6 (α:a), taking into account that it had been reported, that the α mating type strains occur in over 90% of the worldwide C. neoformans clinical and environmental isolates (14,24). However, it was recently reported by our group that 96.6% of serotype B isolates are of mating type a (17).…”
Section: Discussionmentioning
confidence: 58%
“…The mating type locus has been associated with virulence, as suggested by Kwon-Chung et al (13), who found that MATα strains were more virulent in a mouse model than the MAT a isolates. Recently it was found that the cryptococcosis outbreak on Vancouver Island, Canada was caused by isolates that were highly virulent mating type α strains belonging to the C. gattii molecular type VGII/AFLP6 (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation